Information trustworthiness as a solution to the misinformation problems in social media - Nurse, J; Agrafiotis, I; Goldsmith, M; Creese, S; Lamberts, K; Price, D; Jones, G (2015)
The advent of the Internet has reshaped the way we communicate and interact in our daily lives. It provides an ideal medium through which we can share information and ideas, form groups, and contribute to a variety of discussions. In this position paper, we focus specifically on the information now available online – especially content from social media – to consider in detail the challenges that such information poses to modern-day society. Typical examples of challenges include the prevalence of mistaken information and deliberate misinformation and rumours. With an understanding of these challenges, we then introduce the notion of information-trustworthiness measures as a potential solution to the problem of misinformation in social media. The idea here is to use quality and trust metrics to assess information, and then, based on values attained, advise users whether or not they should trust the content. This paper extends our previous research in the field by assessing the misinformation problem in much greater detail, and also presenting our current agenda for future work.